ENHANCING LEARNING OUTCOMES DESCRIPTIVE TEXT ENGLISH THROUGH COOPERATIVE LEARNING - Kartino Kartino (Program Pascasarjana Universitas Negeri Jakarta, 2019)
The purpose of this study is to improve student learning outcomes in learning Descriptive Text. The subjects were students of Class 7E SMPN 2 Cirebon with 42 people. This research method uses a combined method. This research was conducted in 2 cycles. Quantitative findings increased from an average value of 64 to 90 or an increase of 40.63%, while in groups from 75.6 to 94 or an increase of 24.34%. The questionnaire given in the form of a feedback sheet of students 99.392% answered Yes and 0.608% answered No, while the qualitative findings show an increase in learning Descriptive Text. In conclusion, Language Learning English can be Increased by using